Production Cost Budgeting and Evaluating using Android Device Application - ., Isnaeni; Agung Gde Agung, Anak; Widayanti, Asti (International Journal of Engineering and Technology, 2019)
For manufacturing companies, production costs are the largest cost components. These costs consist of raw material cost, labor cost and factory overhead cost. Miscalculation of production costs can make manager difficult to assign company profit. Therefore, the calculation of profit using profitability rasio, plays important role for measure of compay eficiency. This research proposes an application for calculating production cost budget, from calculation of the cost of raw materials, labor costs, and factory overhead costs. This application can also evaluate budget realization, and perform variance analysis. Android platform was chosen for its mobility of use and operating system popularity. With system proposed, the company can set standards and budgetary target, determine their production cost precisely and evaluate budget realization. Costs caused by over or under buying raw material can be avoided. Furthermore, variance analysis generated can be used as performance measurement and control at the level of responsibility center (such as unit, department or division) of the company.Â